Cancer-Related Visits to the Emergency Department: Trends and Patient Characteristics at Adam Malik General Hospital Medan - Kamal Basri Siregar; Yolanda Rahayu; Yongki Suganda; Aze Andrea (Sumatera Medical Journal, 2023)
Background: The prevalence of cancer cases globally is increasing rapidly, especially in emergency department (ED) visits. Usually, cancer patients come for acute signs and symptoms of a still undiagnosed malignancy, management of treatment-related side effects, co-morbidities, and palliative care. Objective: To identify the demographic characteristics of cancer patients, reasons for ED visits, and associated factors of oncologic patients. Methods: A prospective cross-sectional study was conducted from July 2022 - June 2023 at the ED of H. Adam Malik Hospital Medan with 392 oncologic patients. Data were collected using the Integrated System Application of Hospital (STARS) database. Results: The percentage of women (69%) was two times higher than men (31%), with 82% being 18- 64 years old. Breast was the most common location of malignancy for 21.4%, followed by gastrointestinal malignancy for 20.1%. The most common reason for ED visits was pain, followed by gastrointestinal symptoms. The ratio of patients who were discharged and hospitalized was 50:50, while the mortality rate was none. Conclusion: The most common primary diagnosis was breast malignancy in women and gastrointestinal malignancy in men. The majority of ED visits were for the management of treatment-related side effects and palliative care.